Computational Study on the C–Heteroatom Bond Formation via Stille Cross-Coupling Reaction: Differences between Organoheterostannanes Me3SnAsPh2 vs Me3SnPPh2 - Sosa Carrizo, Daiann (2014)
The formation of C–heteroatom bonds through the Stille cross-coupling reaction has been explored computationally within the density functional theory framework. To this end, the reaction profiles of the processes involving different aryl halides (PhCl, PhI) and heterostannanes (Me3SnZR2, Z = As, P; R = Ph, Me) in the presence of palladium catalyst have been investigated and compared to gain more insight into the differential reactivity observed experimentally. In addition, the main features of the reaction steps where the heterostannanes are involved, namely, the transmetalation and reductive elimination reactions, have been analyzed in detail. It was found that the overall relative reaction profile for the transmetalation step involving heterostannanes with Z = P is energetically favored over that involving species having Z = As, which agrees with the experimental observations. This can be mainly ascribed to the relative strength of the Sn–Z bond, which is broken during the transmetalation step (Sn–P < Sn–As).